2023
DOI: 10.11124/jbies-22-00300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone administration for postoperative nausea and vomiting prophylaxis on glucose levels in adults with diabetes undergoing elective surgery: a systematic review and meta-analysis

Andrew Dimmen,
Sara Timko,
Jennifer Greenwood
et al.

Abstract: Objective: The objective of this review was to evaluate the effect of intravenous dexamethasone given intraoperatively for postoperative nausea and vomiting prophylaxis on maximal blood glucose level within the initial 24 hours following elective surgery in patients with diabetes. Introduction: Postoperative nausea and vomiting is a prevalent adverse effect of anesthesia that leads to morbidity, increased health care costs, and unanticipated hospital ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(480 reference statements)
0
1
0
Order By: Relevance
“…11 Presented in this month's issue of JBI Evidence Synthesis, our team conducted a systematic review that pooled results from 11 studies that demonstrated a small but consistent increase in blood glucose levels among patients with diabetes who received a single intravenous dose of 4 to 10 mg of dexamethasone. 12 The clinical implications of this increase in blood glucose levels is likely negligible and easily managed with exogenous insulin administration if required, 13 reinforcing the safety and effectiveness of combination therapy, including dexamethasone. Additional benefits beyond alleviation of PONV to support administration of dexamethasone include reduced systemic inflammation and pain reduction.…”
mentioning
confidence: 99%
“…11 Presented in this month's issue of JBI Evidence Synthesis, our team conducted a systematic review that pooled results from 11 studies that demonstrated a small but consistent increase in blood glucose levels among patients with diabetes who received a single intravenous dose of 4 to 10 mg of dexamethasone. 12 The clinical implications of this increase in blood glucose levels is likely negligible and easily managed with exogenous insulin administration if required, 13 reinforcing the safety and effectiveness of combination therapy, including dexamethasone. Additional benefits beyond alleviation of PONV to support administration of dexamethasone include reduced systemic inflammation and pain reduction.…”
mentioning
confidence: 99%